Sketch-Based Modeling in Mechanical Engineering Design: Current Status and Opportunities. (September 2022) - Camba, Jorge D.; Company, Pedro; Naya, Ferran
Abstract: Sketch-Based Modeling (SBM) is a field of study that focuses on the automatic creation of 3D models from freehand drawings. Today, two related branches coexist: one aimed at facilitating input for 3D content creation, and the other aimed at routing engineering designs into CAD/CAM/CAE. The latter is the goal of this position paper. Early attempts concentrated on the problem of line-drawing interpretation, but efforts switched toward geometric reconstruction as the "inverse projection" problem became the most challenging step to produce 3D models from 2D line-drawings. The term SBM was popularized when sketches began to displace line-drawings as main input. In the context of engineering design, interest in SBM has somewhat decreased, as studies have shown that current SBM tools are not as usable as paper and pencil sketches, nor do they yet provide any additional value to traditional media. Furthermore, engineers feel reasonably comfortable with current Mechanical CAD (MCAD) paradigms based on parametric modeling, and fail to recognize the potential benefits of interacting with computers via sketches. However, new technological trends such as personal fabrication and the democratization of CAD and manufacturing can significantly benefit from improved SBM tools. In this paper, we conduct a meta-review of the SBM literature which we view as a combination of three elements: geometry (shape), psychology (perception), and engineering (function). We advocate for a new approach to SBM based on reformulating the weights of these elements as an approach for searching the set of intentions in sketches conveyed through cues which, when perceived, reveal regularities and features of the object. Finally, we consider quality of CAD models not just as error-free models, reusable models, or even models that convey design intent, but models that consider these interrelated aspects as a whole. B-Rep models produced by current SBM approaches are "dumb models" without parametrization or procedures required to enable reusability and ensure that the design intent of the sketch is properly conveyed. We advocate for improved analysis approaches aimed at revealing higher-level design information embedded in engineering sketches, as a critical stage to generate richer 3D MCAD models. Graphical abstract: Highlights: A review of Sketch-Based Modeling (SBM) for Engineering Design is provided. Two different branches of SBM research coexist: one geared toward "artistic" purposes and the other governed by "engineering" principles. The two branches must be studied separately, because of the fundamentally different goals of artistic vs. engineering sketches and the different nature of the 3D models that must be generated. While the automatic conversion of artistic sketches into 3D models has made significant progress in recent years, the problem of producing CAD models with controllable, semantic, and parametric solid geometry has not yielded significant contributions to the scholarly literature. Future opportunities, research directions, and recommendations on SBM approaches for engineering design are discussed.